Computational Study of Trisindoline 5 Against Overexpressed EGFR Protein on Breast Cancer Stem Cell - Nurhayati A.P.D.; Fatoni M.; Santoso M.; Wati F.A. (BIO Web of Conferences)
The current treatment to control the proliferation rate of breast cancer is still not optimal due to the presence of breast cancer stem cells (BCSCs) which are resistant to several chemotherapy agents. Epidermal Growth Factor Receptor (EGFR) may promote the survival of BCSCs. The existing inhibitory drugs used to treat the EGFR that act as the master regulator of the signaling network still have a limited response in breast cancer. Trisindoline is an indole trimer alkaloid natural compound that provide a cytotoxic effect on cancer cells. In 2021, modification of trisindoline has been synthesized into trisindoline 5. This study aims to analyze the interaction between trisindoline 5 and EGFR through in silico. Data retrieval trisindoline 5 using ChemDraw, doxorubicin as positive control from PubChem, EGFR from RCSB database. Docking was done using AutoDock Vina and the results were visualized using Biovia Discovery Studio. The binding affinity of trisindoline 5 is lower than doxorubicin to the EGFR. Trisindoline 5 can inhibit EGFR binding site on some amino acids and forms hydrogen bonds that predicted to be more stable. This research informed that trisindoline 5 might be potential for developing novel therapeutic drug against BCSCs.